WST-8 analysis of cell viability during osteogenesis of human mesenchymal stem cells - Stoddart, Martin J (Methods in molecular biology (Clifton, N.J.), 2011)
WST-8 is one of the newer generation formazan-based dyes, which release the converted product into the medium in a soluble form. This allows for a non-destructive determination of viability enabling the cells to be subject to further investigations. This is a major advantage in cases where cell phenotype is being investigated and data such as matrix synthesis is correlated to cell number. This chapter describes the use of WST-8 to normalise alkaline phosphatase activity.